Sektor pośrednictwa finansowego polem konkurencji między miastami (gminami) w Polsce - Korenik, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper refers to the emulation of a modern city (community) in the following two areas: "win domestic and foreign investors" and "localization of financial institutions". It presents in a synthetic way the recent directions of change and development trends in the sector of financial mediation in Poland after Poland's joining the European Union. In this aspect was indicated a chance that rivaling among themselves cities (comunnities) have to use. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 38-47